M13 Aquatherapy for people with huntington's disease. (13th September 2016) - Fossmo, Hanne Ludt; Thornes, Ingrid; Lie, Anette
Abstract : Background: Vikersund Rehabilitation Centre has intensive rehabilitation groups for people in early to middle stages of Huntington's disease (HD). For the last 5 years there has been between twenty-five and thirty different HD patients participating in the program which consists of 3 weeks of inpatient rehabilitation 3 times per year. The multidisciplinary approach to the rehabilitation focuses on both active training as well as goals in improving activity and participation in everyday life. Aqua therapy is one of the many group trainings available as part of the program for the HD patients. Aims: To improve the physical capacity in a challenging yet safe environment and to be active without fear of falling. To reduce chorea and make them feel relaxed as they float around in the water. Methods: Aqua therapy sessions consist of groups of up to 6 HD patients and one instructor. The session is performed in a warm (34° C) shallow (chest deep) pool. The session has a thirty minutes exercise component with aerobic and resistance type exercises as well as exercises for coordination and stability training. It is a key feature that the instructions and movements are easy and accurate, and that the participants can follow the instructors movements. Exercises are tailored to the individual's ability. The exercise component is followed by a fifteen minutes cool-down and relaxation component where the participants lay in the water using floating devices and neck pillows. Results: Patients report high levels of adherence and satisfaction and the instructor reports of lower levels of chorea while the participants float in the water. After almost 6 years of aquatherapy for participants with HD there has not been a single adverse event where the participants have needed the help from an instructor or lifeguard in the water. These results are supported by research done on other neurodegenerative disorders and aquatherapy. Conclusions: Aqua therapy for people in early to middle stages of HD is safe, tolerable and pleasurable for the participants, but there needs to be done more research as to the specific effect of the therapy.